Where should the birds fly after the last sky? Images and voices of women of the Iraqi diaspora in the United Kingdom - Ali, Farah (Diaspora Studies, 2018)
This paper tackles the formation of identity of a group of first generation Iraqi women in the diaspora, who went to the northern city of Kingston upon Hull in England, after 2003. The paper, therefore, focuses on three identity categories, viz. religious, cultural, and linguistic to see how the diaspora women negotiate the terms of their subject position as a first generation diaspora group in the United Kingdom, UK. The researcher used ethnography and interviewing in the study. Fifteen Iraqi women were interviewed in order to understand what ‘home’ means to them. The paper also examined the Iraqi women’s understanding of ‘citizenship’ and the role social media sites had played in creating virtual spaces for them, especially by feeding into their personal and cultural identities in the diaspora. The research is situated within the sphere of feminist political philosophy of diaspora in connection with the women’s rights to have identities different from the dominant culture in their host countries. Moreover, the researcher reviews three hypotheses bearing on intercultural relations: the multiculturalism hypothesis, the integration hypothesis, and the contact hypothesis. (Berry, John W. 2013. “Intercultural Relations in Plural Societies: Research Derived from Multiculturalism Policy.” Acta De Investtigacion Psicologica 2 (3), 1122–1135) By testing the three intercultural hypotheses against the results of the conducted research, the study concludes that the Iraqi diaspora community is not a homogenous entity as it includes minorities within the minority. Therefore, there needs to be a system that respects diversity, hence the researcher supports the continuation of multiculturalism policy in hope of developing better intercultural relations.